Physical and magnetic properties of iron oxide nanoparticles with a different molar ratio of ferrous and ferric - Azza M. Mazrouaa; Manal G. Mohamed; Mohamed Fekry (Egyptian Journal of Petroleum)
The magnetite (Fe3O4) nanoparticles were synthesized with the same reaction conditions like co-precipitation method, molar ratio, and raw materials, but their magnetization values were not the same. This due to the change of some properties of ferrous oxide (Fs) nanoparticles when exposed it to the air. So this work suggested the core-shell design of magnetite nanoparticles (MA), this core-shell was prepared from ferric oxide (Fc) nanoparticles coated with sheets from ferrous oxides (Fs). The magnetic properties of iron oxide nanoparticles with different molar ratios of ferrous and ferric were studied via co-precipitation with NaOH. The crystallographic and phase structure of prepared iron oxides nanoparticles were investigated by employing Wide angle X-ray diffraction (WAXD), Particle size and zeta potential, Vibrating Sample Magnetometer (VSM), X-ray fluorescence (XRF), Fourier transforms infrared spectroscopy (FTIR) and High resolution transmission electron microscopy (HR-TEM). The changed magnetic moment of iron oxide nanoparticles was attributed to the presence of different a concentration of manganese atoms. Keywords: Magnetite nanoparticles, Co-precipitation, Antiferromagnetic, Ferromagnetic, Ferrite